EVALUATION OF MYRTUS COMMUNIS FLAVONOID AS ANTIDER-MATOPHTIC AND KERATINASE INHIBITIOR - & et al., Abbas (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was applied for  extraction  flavonoid compounds  from Myrtus   communis (aerial part)and detection of its effectiveness on growth of one of dermatiphytic isolates and keratinase activity, Trichophyton mentagrophytes was the most common isolates which was obtained   with frequency (66%),  the identification and quantitation of flavonoids was carried out by thin layer and high performance liquid chromatography. The results showed that each 100 g of aerial part of the plant  contained 850 mg total flavonoids as rutin).The HPLC chromatogram for M. communis flavonoid extract revealed that, M. communis  flavonoid extract contained Rutin, Quercetin, Apigenin, Kaempferol, Luteolin . The inhibitory effect of flavonoid against Trichophyton mentagrophytes and keratinase activity was evaluted. The higher effect was observed at concentration 10 mg/ml against fungal isolate .The minimum inhibiter concentration was  at 3mg/ml while the higher inhibition of keratinase activity was obtained at concentration 5mg/ml with 25% remaining enzyme activity.